Correlação entre doença inflamatória intestinal e doença do refluxo gastroesofágico - revisão de literatura - Almeida, Saulo Santiago (2019)
The enteric nervous system and immune system interact intensely in healthy individuals and in various intestinal diseases. The existence of a relationship between intestinal and esophageal motility is being studied since the end of the 19th century. Several studies have already demonstrated the increased prevalence of gastroesophageal reflux disease (GERD) in patients with irritable bowel syndrome (IBS). However, there is little reference to the relationship between GERD and inflamatory bowel disease (IBD). Although they are distinct entities, IBD and GERD present changes in gastrointestinal motility whose pathogenesis is not fully known and may be related. Our main objective is to gather information available in the literature on esophageal motility alterations in patients with IBD. For this, we carried out a review of the literature in 4 databases between 1990 and 2018. Initially, 316 articles were found, of which 9 met the inclusion criteria. We observed that in the majority of studies, there was a higher prevalence of GERD patients with IBD, and the intensity of reflux symptoms was lower when compared to the control group.